2014
DOI: 10.3109/14992027.2013.862599
|View full text |Cite
|
Sign up to set email alerts
|

An Australian version of the acceptable noise level test and its predictive value for successful hearing aid use in an older population

Abstract: While the Australian ANL test showed several similar characteristics to previous versions of the test, low test-retest reliability raised questions about its clinical value as a predictor for long-term hearing aid use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 32 publications
1
23
3
4
Order By: Relevance
“…The results of the HA-Use revealed that the ANL of full-time users (7.5 dB) was higher (poorer) than that of part-time (4.9 dB) and non-users (4.5 dB). Although the difference was not statistically significant, the trend of the findings by Walravens et al (2014) was contrary to Nabelek et al (2006).…”
Section: Introductioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The results of the HA-Use revealed that the ANL of full-time users (7.5 dB) was higher (poorer) than that of part-time (4.9 dB) and non-users (4.5 dB). Although the difference was not statistically significant, the trend of the findings by Walravens et al (2014) was contrary to Nabelek et al (2006).…”
Section: Introductioncontrasting
confidence: 63%
“…However, several studies (Olsen et al, 2012; Schwartz & Cox, 2012; Walravens et al, 2014; Table 1) did not demonstrate a clear association between ANL and hearing aid outcome. In a cross-sectional study, Olsen et al (2012) recruited 63 adults whose mean hearing aid experience was 11 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walravens et al, 2014). Participants were given a handheld wireless keypad that was programmed to change the level of stimuli presented to the loudspeaker array.…”
Section: Methodsmentioning
confidence: 99%
“…In order to assess the subjective benefit of the two beamformers, we also incorporated a measurement of the acceptable noise level (ANL), the poorest SNR at which a person is willing to listen to speech (Nabelek et al, 1991). Recent studies suggest that the ANL tends to be positive (Olsen et al, 2012a; Olsen et al, 2012b; Walravens et al, 2014), as opposed to SRTn measures which generally focus on negative SNRs. Thus the inclusion of the ANL test had the advantage of assessing the benefit of the beamformers at higher SNRs, where it is often argued that most real-world communication occurs (Smeds et al, 2015).…”
Section: Introductionmentioning
confidence: 99%